GENDER PERCEPTIONS IN USING NON-CASH TRANSACTIONS WITH THE TECHNOLOGY ACCEPTANCE MODEL (TAM) APPROACH IN THE COMMUNITY OF PANTA PAJU HAMLET SORO LAMBU KAB. BIMA - Ratnasari, Desi; Hasanah, Shofia Mauizotun (UIN Mataram, 2023)
This study aims to determine the perception of Gender in using Non-Cash transactions with the Technology Acceptance Model (TAM) approach in the Panta Paju Hamlet community. TAM is one of the theories about the use of information technology systems that is considered very influential and is generally used to explain individual acceptance of the use of information technology systems. TAM consists of two indicators, namely influenced by attitudes through perceived ease of use and perceived usefulness. The results of this study state that ease and usefulness between men and women. There are 20 male and female informants, of which 10 men and 10 women stated that those who feel a lot of convenience and usefulness are female informants, this is because female informants often use non-cash transactions compared to men. These results can be represented that 100% of women feel the convenience and benefits of non-cash transactions, 50% of men feel the convenience and 50% do not feel the benefits.